If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1y = 13 Solving 5x + -1y = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 5x + -1y + y = 13 + y Combine like terms: -1y + y = 0 5x + 0 = 13 + y 5x = 13 + y Divide each side by '5'. x = 2.6 + 0.2y Simplifying x = 2.6 + 0.2y
| -3(6x+8)=-24 | | 15*2-34x+15=0 | | 7(7c+1)-4c=13(c-2)+3 | | 2x^2-5y^2=7 | | 10-4x=193 | | 14w=91 | | 1d+(1d*4-12)=(1d*3) | | 4(x+y+z)=xyz | | 4x=7y+10 | | T-66=-55 | | 6(2x+2)=108 | | 5x^4-12x^3=0 | | 14-3(5m-12)=1-(20m+1) | | 15x^5y+35x^3y^3= | | 10+x=50 | | 2u=26 | | -(3y+3)-(-2y-6)=3 | | 5+(x+y+z+t)+10=2xyzt | | 3x-5y=8 | | 1+y+y^2+y^3+y^4=t^4 | | 78=-2(m+3)+3 | | 2a+3a+4a=5a-48 | | x^2+14x+49=11 | | 1+y+y^2+y^3=t^3 | | .5(12n-4)=14-10n | | 6y^2=13y-6 | | P+14=15.7 | | 6y=13y-6 | | 4n-2=n-8 | | 20-92=4(15-w) | | 1/2(12n-4)=14-10n | | 23x+53y=109 |